Pengaruh Komposisi Tubuh terhadap Daya Ledak Otot Tungkai Pemain Sepak Bola Liga 1 Persija Jakarta - Subyakto, Ricky Cannavaro; Pamungkas, Hari; Kurniawan, Rubbi; Nidomuddin, Muhammad; Yusuf, Havid (SPRINTER: Jurnal Ilmu Olahraga, 2024)
Football can be defined as a high-speed game with running while carrying the ball or not and constant movement both for attack and defense. However, with high speed, power, and skill, the factor that can limit their performance is the consideration of the weight of the football player. Weight can affect an important role in the game if it hinders the player's running, speed of movement and when kicking the ball. Leg muscle explosive power is a very important variable in assessing the level of muscle power produced by the lower leg muscles. Therefore, leg muscle explosive power is often used as an important predictor of performance in football sports that require skills in kicking the ball. This study aims to determine the effect of body composition on leg muscle explosive power in Liga 1 Persija Jakarta soccer players. This study is an experimental type through a quantitative descriptive approach (based on numerical data). The research sample was 17 players. The test instruments used were anthropometric tests and power jump tests. Data analysis used SPSS IBM 25. The results of the post-test analysis obtained an average of 59.1271 with a significance of >0.05 (p = 0.031). In conclusion, there is an influence of body composition on the explosive power of the leg muscles of Persija Jakarta soccer players.